2013
DOI: 10.1007/s00259-013-2484-x
|View full text |Cite
|
Sign up to set email alerts
|

SUVmax of 2.5 should not be embraced as a magic threshold for separating benign from malignant lesions

Abstract: Lesions of an indeterminate nature are often encountered in images such as those from CT and MRI. Examples include solitary pulmonary nodules and various incidentalomas that may be found in any body region. FDG PET can be useful in differentiating benign from malignant lesions, given the fact that malignant lesions generally have a higher glycolytic rate and consequently higher FDG uptake. Both visual image interpretation and (semiquantitative) standardized uptake value (SUV) measurements may be used for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 15 publications
1
31
2
3
Order By: Relevance
“…Nguyen stated that a common threshold value for different sites was not feasible, but also reported SUVmax threshold >3.6 as highly sensitive and specific for pulmonary nodules [51]. Besides these findings, in some studies, it has been shown that quantitative analysis by PET scan did not improve accuracy [52][53][54]. Lobrano et al [55] investigated the effect of SUV of pulmonary mass in differentiating whether the masses were benign or malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen stated that a common threshold value for different sites was not feasible, but also reported SUVmax threshold >3.6 as highly sensitive and specific for pulmonary nodules [51]. Besides these findings, in some studies, it has been shown that quantitative analysis by PET scan did not improve accuracy [52][53][54]. Lobrano et al [55] investigated the effect of SUV of pulmonary mass in differentiating whether the masses were benign or malignant.…”
Section: Discussionmentioning
confidence: 99%
“…El FDG puede ser útil para distinguir entre lesiones benignas y malignas, ya que la evidencia de malignidad tiene generalmente una tasa glucolítica más alta y por consiguiente mayor captación del FDG 12 . Algunos usan el umbral máximo del valor de captación estandarizado (SUV) de 2,5 para distinguirlos 12 . Sin embargo, las mediciones SUV dependen de varios parámetros: equipo utilizado, la física (scanner de variabilidad, cambios de parámetros de reconstrucción, error de calibración entre el scanner y calibrador de dosis, desfase entre scanner y calibrador de dosis, uso de material de contraste en TEP/TC, variabilidad interobservador) y factores biológicos (composición de peso, medición de tamaño corporal, corrección de glucosa en la sangre, equipo de captación post inyección, movimiento respiratorio) 12,13 .…”
unclassified
“…Algunos usan el umbral máximo del valor de captación estandarizado (SUV) de 2,5 para distinguirlos 12 . Sin embargo, las mediciones SUV dependen de varios parámetros: equipo utilizado, la física (scanner de variabilidad, cambios de parámetros de reconstrucción, error de calibración entre el scanner y calibrador de dosis, desfase entre scanner y calibrador de dosis, uso de material de contraste en TEP/TC, variabilidad interobservador) y factores biológicos (composición de peso, medición de tamaño corporal, corrección de glucosa en la sangre, equipo de captación post inyección, movimiento respiratorio) 12,13 . Además, los procesos infecciosos e inflamatorios pueden conducir a un aumento de captación del FDG mucho mayor que el SUV 2,5, principalmente en lesiones infecciosas agudas 12,13 .…”
unclassified
See 1 more Smart Citation
“…It is well known that SUV measurements can be affected by many issues, such as the reconstruction algorithm, the scanner used, the interval between tracer injection and the acquisition, the partial volume effect and so on [14]. Furthermore, SUV concerns information only on tumour metabolic activity and does not consider the overall tumoural volume.…”
mentioning
confidence: 99%